Élő Rádiókabaré. Tavaszi hadjárat
Hócipő cabaret in Veszprém, Tivadar Farkasházy, Tibor Selmeczi, Mátyás Usztyics, Imre Bajor, Sándor Fábry, Judit Csehák, István Bethlen parliamentary representatives, László Juszt, András Nagy Bandó, Róbert Koltai, István Éles, Gusztáv Megyesi, Iván Bagi, Szilveszter Gábor